1999
DOI: 10.1046/j.1469-8137.1999.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and spatial distribution of viruses in natural populations of Brassica oleracea

Abstract: We report a survey of four viruses (beet western yellows luteovirus (BWYV), cauliflower mosaic caulimovirus (CaMV), turnip mosaic potyvirus (TuMV), turnip yellow mosaic tymovirus (TYMV)) in five natural populations of Brassica oleracea in Dorset (UK). All four viruses were common ; 43% of plants were infected with BWYV, 60% with CaMV, 43% with TuMV and 18% with TYMV. For each virus there were significant differences in the proportion of infected plants among populations, which were not completely explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 53 publications
2
61
0
5
Order By: Relevance
“…However, one recent study has shown competitive displacement of fungal pathogen strains in locusts (Thomas et al 2003), and it would be valuable to determine the degree to which this occurs in invertebrate pathogens that fit the model of vector-borne disease. Competitive displacement has also been found in plants, as well as multiple infections of plant and insect hosts or patches (Power 1996, 2000, Raybould et al 1999. However, with only the insects dispersing parasites, parasite competitiveness is the least sensitive of the parameters in the model (Fig.…”
Section: Recipes For Challenging Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one recent study has shown competitive displacement of fungal pathogen strains in locusts (Thomas et al 2003), and it would be valuable to determine the degree to which this occurs in invertebrate pathogens that fit the model of vector-borne disease. Competitive displacement has also been found in plants, as well as multiple infections of plant and insect hosts or patches (Power 1996, 2000, Raybould et al 1999. However, with only the insects dispersing parasites, parasite competitiveness is the least sensitive of the parameters in the model (Fig.…”
Section: Recipes For Challenging Predictionsmentioning
confidence: 99%
“…We have dealt with superinfection as this is mathematically more tractable than multiple infection, but both represent the degree to which a parasite controls the host in the face of competition. There have been efforts to assess multiple infection of individuals or patches in the field (Lam and Marshall 1968, Power 1996, Raybould et al 1999, Armstrong and Rico-Hesse 2001. For invertebrate diseases, it may be too early to apply our predictions to individual systems given the lack of empirical data on parasite competition.…”
Section: Recipes For Challenging Predictionsmentioning
confidence: 99%
“…One of the major environmental safety issues over transgenic crops relates to the consequences of gene flow into wild relatives in regard to increased fitness and enhanced weediness (Dale, 1992;Hancock et al, 1996;Kareiva et al, 1994;Raybould, 1999;Rissler and Mellon, 1996;Snow and Palma, 1997). Indeed, genetically engineered crops, as well as conventionally bred crops, have the potential to spontaneously hybridize with their sexually compatible wild, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…TuMV Potyviridae ( , family) Potyvirus ( , genus) . 300 89 (Raybould , 1999;Sánchez , 2003). Bromoviridae ( , family) Cucumovirus ( , genus) CMV ,…”
Section: Turnip Mosaic Virus(tumv)mentioning
confidence: 99%